Determinan Keputusan Pembelian Jilbab Melalui Online Shop - Ramadhanty, Rizki Nadia; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2020)
The development of information and communication technology is getting faster, all can be accessed easily via the internet, this has an impact on the innovation of shooping activities into online shopping. This research aims to determine the influence of lifestyle, trust, ease, price, time and cost efficiency, reference groups, quality of information, and promotion of hijab purchasing decisions through online shop. The type of research is quantitative with quantitative descriptive methods with some analysis techniques used are t test, F test and coefficient of determination test (R2). The results showed that lifestyle, price, time and cost efficiency, reference groups, quality of information, and promotion affect the purchasing decisions hijab through online shop, while trust and ease do not affect purchasing decisions hijab through an online shop. F test results show that lifestyle, trust, ease, price, time and cost efficiency, reference groups, quality of information, and promotion together have and affect on the purchasing decisions hijab on female students S1 Islamic Economics at State University of Surabaya through online shop.